The Yield Response of Wheat to Zinc Fertilization (Journal of Science Foundation, 2013)
The experiment on wheat to zinc fertilization was carried out at the Regional Agricultural Research Station, Agricultural Research Sub-Station, and Special Crop Research Stations of BARI and at Farmers field. The grain yield was increased with increasing application of zinc upto 6 kg/ha but beyond that the level the yield was declined. The highest yield (3.87t/ha) was obtained in 6 kg Zn/ha under Amnura series as compare to Nachole and Lauta series. The lowest yield was obtained in Nachole series (3.07 t Zn/ha) under Deep Grey Terrace Soil. In Gangachara too, the grain yield of wheat was increased with increasing levels of zinc upto 6 kg Zn/ha beyond that it was declined. The highest yield (5.58t/ha) was obtained in 6 kg Zn/ha under Gangachara series and compare to Kaunia and Sonatola series. The lowest yield was obtained (3.92t/ha) in Kaunia series under Grey Floodplain Soils.The grain yield of wheat was significantly increased upto 12 kg Zn/ha in Calcarious Dark Grey Floodplain and Calcarious Brown Floodplain Soils and the order of increase was Zn12>Zn9>Zn6 >Zn3>Zn0. The highest yield (5.50 t/ha) was recorded in 12 kg Zn/ha. The order of the yield was Ishardi 5.50 t/ha > Sara5.47 t /ha> Gopalpur 5.13 t /ha>Darsona 2.91t/ha was recorded under Calcarious Dark Grey Floodplain and Calcareous Brown Floodplain Soils. DOI: http://dx.doi.org/10.3329/jsf.v9i1-2.14644 J. Sci. Foundation, 9(1&2): 15-25, June-December 2011